RELATIONSHIP BETWEEN MOTHER AND FAMILY FACTORS TO THE INCIDENCE OF ACUTE RESPIRATORY TRACT INFECTION (ARI) IN UNDER-FIVES AGED 1-5 YEARS AT PANEI TONGAH HEALTH CENTER SIMALUNG DISTRICT - Muharti Sanjaya; Ismi Noer Fadilah; Edwin Tony Sohdin Martua Simanjuntak (Universitas Efarina, 2021)
The problem in this study is the relationship between maternal factors and family factors on the incidence of acute respiratory infection (ARI) in toddlers aged 1-5 years at the Panci Tongah Health Center, Simalungun Regency. This study aims to determine the relationship between maternal factors and family factors on the incidence of respiratory infections. Acute Respiratory Tract Infection (ARI) in Toddlers Aged 1-5 Years at the Panei Tongah Health Center, Simalungun Regency This type of research is an analytic survey study with a cross sectional approach. The population in this study were mothers who had toddlers aged 1-5 years who visited the Panet Tongah Health Center, Simalungun Regency, with a total of 34 people. Saturated Sampling The instrument used in this study was a questionnaire. The data obtained in the study were processed using the Chi Square statistical test with a 0.05. The results showed that the p values ​​of the several factors studied were as follows 1) mother's age p value = 0.319, 2) mother's education p value = 0.356, 3). mother's knowledge p value = 0.001; 4) smoking habits in the house p value - 0.007; 5) use of mosquito coils while sleeping p value = 0.009, 6). use of cooking fuel with firewood p value = 0.029. The results of the research and discussion concluded that there was a significant relationship between the relationship between maternal factors and family factors on the incidence of acute respiratory infection (ARI) in toddlers aged 1-5 years at the Panei Tongah Health Center.